Oxygen-free copper sheet for ceramic copper-clad plate, preparation method of oxygen-free copper sheet and ceramic copper-clad plate
By controlling the deformation rate of rough rolling and finish rolling and annealing treatment, oxygen-free copper sheets that meet the requirements of ceramic copper-clad laminates are prepared, solving the problem of unstable mechanical properties in the existing technology and achieving excellent welding bonding rate and peel strength.
Patent Information
- Application Number
- CN202511124006.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-11-18
AI Technical Summary
Existing technologies have failed to effectively control the mechanical properties of oxygen-free copper sheets used in ceramic copper-clad laminates, affecting the welding bond rate and peel strength.
By controlling the deformation rates of rough rolling and finish rolling, and performing annealing treatment between the two, oxygen-free copper sheets that meet the requirements of ceramic copper-clad laminates are prepared. The specific steps include melting and casting copper sheet raw materials, hot rolling, rough rolling, annealing and finish rolling, and strictly controlling the deformation rate and annealing temperature of each pass.
The hardness, tensile strength, and elongation of the oxygen-free copper sheet are improved, ensuring excellent weld bonding rate and peel strength, thus meeting the application requirements of ceramic copper-clad laminates.
Smart Images

Figure BDA0005543775450000121 
Figure BDA0005543775450000131
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of copper plate, in particular to a kind of oxygen-free copper sheet for ceramic copper-clad plate and its preparation method and ceramic copper-clad plate. BACKGROUND
[0002] Ceramic copper-clad plate is a kind of composite substrate which is bonded by welding oxygen-free copper sheet and ceramic substrate at high temperature. It has high thermal conductivity, high electrical insulation, high mechanical strength, low expansion and other characteristics of ceramic, and also has high electrical conductivity and excellent welding performance of oxygen-free copper. In order to ensure its final performance, high requirements are put forward for the bonding rate and peel strength of ceramic copper-clad plate. The mechanical properties of oxygen-free copper sheet as the main material will directly affect the bonding rate and peel strength of ceramic copper-clad plate.
[0003] CN116042983A discloses a copper plate preparation method for ceramic copper-clad plate. The method first melts and casts copper plate raw materials into copper ingot, then mills the surface after hot rolling, and then roughens and anneals to finish rolling to obtain finished copper plate. The finished copper plate is annealed and subjected to multi-pass rolling and cyclic annealing, and finally the copper plate is obtained.
[0004] CN106216423A discloses a production process of high-conductivity oxygen-free copper strip for ceramic copper-clad substrate. The method includes high-purity copper melting and casting, up-drawing continuous casting copper rod, continuous extrusion, cold rolling, annealing, cold rolling, straightening, cleaning and passivation, and slitting.
[0005] Although the methods disclosed in CN116042983A and CN106216423A can produce oxygen-free copper strip for ceramic copper-clad substrate, they do not include a method for controlling the mechanical properties of the final copper strip, and the performance of the ceramic copper-clad plate after welding is uncertain.
[0006] Therefore, it is necessary to develop a method for controlling the mechanical properties of oxygen-free copper sheet for ceramic copper-clad plate after welding. SUMMARY
[0007] To solve the above technical problems, the present application provides an oxygen-free copper sheet for ceramic copper-clad plate and its preparation method. By controlling the rolling deformation rate of rough rolling and finish rolling, the mechanical properties of the copper plate meet the production requirements of oxygen-free copper sheet for ceramic copper-clad plate, and the performance is good, so it has wide application prospect.
[0008] To achieve this purpose, the present application adopts the following technical solutions:
[0009] In the first aspect, the present application provides a preparation method of oxygen-free copper sheet for ceramic copper-clad plate, which comprises the following steps:
[0010] (1) melt and cast copper plate raw materials to obtain ingot.
[0011] (2) The ingot described in step (1) is sequentially preheated and hot-rolled to obtain a hot-rolled material.
[0012] (3) The hot-rolled material described in step (2) is rough-rolled, and the deformation rate of each pass of rough-rolling is controlled to be ≤30% to obtain a rough-rolled material.
[0013] (4) The rough-rolled material described in step (3) is annealed to obtain an annealed material.
[0014] (5) The annealed material described in step (4) is finish-rolled, and the deformation rate of each pass of finish-rolling is controlled to be ≤35% to obtain an oxygen-free copper sheet for ceramic copper-clad plate.
[0015] The oxygen-free copper sheet for ceramic copper-clad plate provided by the present application refers to a copper plate material used for subsequent compounding with a ceramic plate. The copper plate material needs to have optimal hardness, tensile strength and elongation rate at the same time, and the welding condition and the peeling strength after welding of the copper plate and the ceramic also need to be considered. The present application strictly controls the deformation rate of each pass of rough-rolling and finish-rolling, which can improve the strength and hardness. The annealing treatment between rough-rolling and finish-rolling can relieve the residual stress after rough-rolling, thereby improving the elongation rate of the copper plate. Research shows that the copper plate obtained by the above preparation method has excellent welding bonding rate and peeling strength after subsequent compounding and welding with the ceramic plate.
[0016] Specifically, the deformation rate of each pass of rough-rolling is controlled to be ≤30%, for example, it can be 10%, 13%, 15%, 17%, 19%, 22%, 24%, 26%, 28% or 30%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0017] The deformation rate of each pass of finish-rolling is controlled to be ≤35%, for example, it can be 10%, 13%, 15%, 17%, 19%, 22%, 24%, 26%, 28%, 30%, 31%, 32% or 35%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0018] Research shows that when the deformation rate of each pass of rough-rolling is greater than 30%, there are defects of poor copper plate shape and large load of rolling equipment; when the deformation rate of each pass of finish-rolling is greater than 35%, there are defects of high copper plate hardness and low ceramic copper-clad plate peeling strength.
[0019] The oxygen-free copper sheet for ceramic copper-clad plate generally requires that the oxygen-free copper plate meets the following mechanical property requirements: Vickers hardness (90-120 Hv), tensile strength (270-390 MPa), and elongation rate (≥2%).
[0020] Preferably, the copper plate raw material of step (1) comprises electrolytic copper and an additive metal.
[0021] Preferably, the purity of the electrolytic copper is 4N or above.
[0022] Preferably, the additive metal comprises any one or a combination of at least two of silver, iron or chromium, wherein typical but non-limiting combinations are a combination of silver and iron, a combination of chromium and iron, and a combination of silver and chromium.
[0023] Preferably, the silver is added in the form of elemental silver.
[0024] Preferably, the iron is added in the form of a copper-iron alloy.
[0025] Preferably, the chromium is added in the form of a copper-chromium alloy.
[0026] Preferably, the content of silver in the ingot of step (1) is controlled to be 10-40 ppm, such as 10 ppm, 14 ppm, 17 ppm, 20 ppm, 24 ppm, 27 ppm, 30 ppm, 34 ppm, 37 ppm or 40 ppm, etc., but not limited to the listed values, and other non-listed values within the range are also applicable.
[0027] Preferably, the content of iron in the ingot is controlled to be 10-25 ppm, such as 10 ppm, 12 ppm, 14 ppm, 15 ppm, 17 ppm, 19 ppm, 20 ppm, 22 ppm, 24 ppm or 25 ppm, etc., but not limited to the listed values, and other non-listed values within the range are also applicable.
[0028] Preferably, the content of chromium in the ingot is controlled to be 10-25 ppm, such as 10 ppm, 12 ppm, 14 ppm, 15 ppm, 17 ppm, 19 ppm, 20 ppm, 22 ppm, 24 ppm or 25 ppm, etc., but not limited to the listed values, and other non-listed values within the range are also applicable.
[0029] Preferably, the content of impurities in the ingot is <100 ppm, such as 50 ppm, 56 ppm, 61 ppm, 67 ppm, 72 ppm, 78 ppm, 83 ppm, 89 ppm, 94 ppm or 99 ppm, etc., but not limited to the listed values, and other non-listed values within the range are also applicable.
[0030] Preferably, the oxygen content in the ingot is < 5 ppm, for example, it can be 0.1 ppm, 0.2 ppm, 0.3 ppm, 0.5 ppm, 0.8 ppm, 1 ppm, 2 ppm, 3 ppm, 4 ppm or 5 ppm, etc., but not limited to the listed values, other values not listed in this range are also applicable.
[0031] The present application requires strict control of the oxygen content in the ingot to be less than 5 ppm, so as to guarantee the mechanical properties of the final copper plate.
[0032] Preferably, the ingot is a square ingot.
[0033] Preferably, the thickness of the square ingot is 100-200 mm, for example, it can be 100 mm, 112 mm, 123 mm, 134 mm, 145 mm, 156 mm, 167 mm, 178 mm, 189 mm or 200 mm, etc., but not limited to the listed values, other values not listed in this range are also applicable.
[0034] Preferably, the preheating temperature in step (2) is 700-900℃, for example, it can be 700℃, 723℃, 745℃, 767℃, 789℃, 812℃, 834℃, 856℃, 878℃ or 900℃, etc., but not limited to the listed values, other values not listed in this range are also applicable.
[0035] The present application preferably controls the preheating temperature in this range, which can have the effect of dynamically softening the microstructure during hot rolling, and can also cause dynamic recrystallization in the copper plate.
[0036] Preferably, the thickness of the material after hot rolling is 10-12 mm, for example, it can be 10 mm, 10.3 mm, 10.5 mm, 10.7 mm, 10.9 mm, 11.2 mm, 11.4 mm, 11.6 mm, 11.8 mm or 12 mm, etc., but not limited to the listed values, other values not listed in this range are also applicable.
[0037] Preferably, step (3) further comprises a face milling treatment before rough rolling.
[0038] Preferably, the face milling treatment removes the surface oxide layer and the edge cracks.
[0039] Preferably, the thickness after rolling in step (3) is 0.7-1.0 mm, for example, it can be 0.7 mm, 0.74 mm, 0.77 mm, 0.8 mm, 0.84 mm, 0.87 mm, 0.9 mm, 0.94 mm, 0.97 mm or 1.0 mm, etc., but not limited to the listed values, other values not listed in this range are also applicable.
[0040] Preferably, the rough rolling is 10-15 passes, for example, it can be 10 passes, 11 passes, 12 passes, 13 passes, 14 passes and 15 passes.
[0041] Preferably, the annealing temperature in step (4) is 250-650℃, for example, it can be 250℃, 295℃, 339℃, 384℃, 428℃, 473℃, 517℃, 562℃, 606℃ or 650℃, etc., but not limited to the listed values, other values not listed in this range are also applicable.
[0042] A large amount of stress and lattice distortion will be generated in the process of rough rolling of copper plate, and the present application preferably controls the annealing temperature in the above range, which is more prone to recrystallization, thereby forming uniform fine grains, which can better eliminate residual stress caused by rough rolling and avoid deformation and cracking during subsequent processing or use.
[0043] Preferably, the annealing time is 1-3h, for example, it can be 1h, 1.3h, 1.5h, 1.7h, 1.9h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, etc., but not limited to the listed values, other values not listed in this range are also applicable.
[0044] Preferably, the number of passes in step (5) is 2-3 passes.
[0045] As a preferred technical solution of the present application, the preparation method comprises:
[0046] (1) The copper plate raw material is melted and cast to obtain an ingot. The content of silver element in the ingot is controlled to be 10-40ppm, the content of iron element is controlled to be 10-25ppm, the content of chromium element is controlled to be 10-25ppm, the impurity content is <100ppm, and the oxygen element content is <5ppm. The ingot is a square ingot. The thickness of the square ingot is 100-200mm.
[0047] (2) The ingot in step (1) is sequentially preheated at 700-900℃ and hot-rolled to obtain a hot-rolled material with a thickness of 10-12mm.
[0048] (3) The hot-rolled base material in step (2) is rough-rolled, the rough rolling is 10-15 passes, and the deformation rate of each pass of rough rolling is controlled to be ≤30%, to obtain a rough-rolled material with a thickness of 0.7-1.0mm.
[0049] (4) The rough-rolled material in step (3) is annealed at 250-650℃ for 1-3h to obtain an annealed material.
[0050] (5) After annealing the material as described in step (4), the material is subjected to finish rolling, the number of passes of finish rolling is 2-3 passes, and the deformation rate of each pass of finish rolling is controlled to be ≤ 35%, to obtain the oxygen-free copper sheet for ceramic copper-clad plate.
[0051] In a second aspect, the present application provides an oxygen-free copper sheet for ceramic copper-clad plate, which is prepared by the method for preparing the oxygen-free copper sheet for ceramic copper-clad plate according to the first aspect.
[0052] Preferably, the thickness of the oxygen-free copper sheet for ceramic copper-clad plate is 0.3-0.5 mm, for example, it can be 0.3 mm, 0.32 mm, 0.35 mm, 0.38 mm, 0.4 mm, 0.42 mm, 0.45 mm, 0.48 mm or 0.5 mm, etc., but is not limited to the listed values, and other values not listed in this range are also applicable.
[0053] Preferably, the hardness of the oxygen-free copper sheet for ceramic copper-clad plate is 90-120 Hv, for example, it can be 90 Hv, 95 Hv, 100 Hv, 105 Hv, 110 Hv, 115 Hv or 120 Hv, etc., but is not limited to the listed values, and other values not listed in this range are also applicable.
[0054] Preferably, the tensile strength of the oxygen-free copper sheet for ceramic copper-clad plate is 270-390 MPa, for example, it can be 270 MPa, 275 MPa, 280 MPa, 285 MPa, 290 MPa, 300 MPa, 320 MPa, 330 MPa, 340 MPa, 350 MPa, 380 MPa or 390 MPa, etc., but is not limited to the listed values, and other values not listed in this range are also applicable.
[0055] Preferably, the elongation of the oxygen-free copper sheet for ceramic copper-clad plate is ≥ 2%, for example, it can be 2%, 2.2%, 2.5%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 6.8% or 7.0%, etc., but is not limited to the listed values, and other values not listed in this range are also applicable.
[0056] In a third aspect, the present application provides a ceramic copper-clad plate comprising the oxygen-free copper sheet for ceramic copper-clad plate according to the second aspect.
[0057] The ceramic copper-clad plate provided by the present application has excellent soldering bonding rate and peeling strength, and excellent performance.
[0058] Compared with the prior art, the present application has at least the following beneficial effects:
[0059] (1) The preparation method of the oxygen-free copper sheet for ceramic copper-clad plate provided by the present application can control the mechanical properties of the oxygen-free copper sheet for ceramic copper-clad plate within the required range by controlling the deformation rate of each rough rolling and each finish rolling, so as to control the performance of the copper plate after welding.
[0060] (2) The preparation method of the oxygen-free copper sheet for ceramic copper-clad plate provided by the present application preferably controls the temperature of preheating and annealing within a reasonable range, cooperates with the deformation rate of rough rolling and finish rolling, and can simultaneously ensure the hardness, tensile strength and elongation of the copper plate.
[0061] (3) The Vickers hardness of the oxygen-free copper sheet for ceramic copper-clad plate provided by the present application is above 90Hv, the tensile strength is above 270MPa, and the elongation is ≥2%. DETAILED DESCRIPTION
[0062] In order to facilitate the understanding of the present application, the present application lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present application and should not be regarded as specific limitations on the present application.
[0063] Embodiment 1
[0064] The present embodiment provides a preparation method of an oxygen-free copper sheet for ceramic copper-clad plate, which comprises:
[0065] (1) The copper plate raw material is melted and cast to obtain an ingot. The content of silver element in the ingot is controlled to be 15ppm, the content of iron element is controlled to be 10ppm, the content of chromium element is controlled to be 10ppm, the impurity content is <100ppm, and the oxygen element content is <5ppm. The ingot is a square ingot; the thickness of the square ingot is 120mm.
[0066] (2) The ingot in step (1) is sequentially preheated at 800℃ and hot rolled to obtain a hot-rolled material with a thickness of 11mm.
[0067] (3) The hot-rolled base material in step (2) is rough rolled, the rolling pass number of rough rolling is 12 passes, and the deformation rate of each pass of rough rolling is controlled to be 25%, to obtain a rough-rolled material with a thickness of 0.75mm.
[0068] (4) The rough-rolled material in step (3) is annealed at 500℃ for 2h to obtain an annealed material.
[0069] (5) The annealed material in step (4) is finish rolled, the pass number of finish rolling is 2 passes, and the deformation rate of each pass of finish rolling is controlled to be 35%, to obtain an oxygen-free copper sheet for ceramic copper-clad plate with a thickness of 0.3mm.
[0070] Embodiment 2
[0071] The embodiment provides a preparation method of oxygen-free copper sheet for ceramic copper-clad plate, and the preparation method comprises the following steps:
[0072] (1) melt and cast a copper plate raw material to obtain an ingot. The content of silver element in the ingot is controlled to be 10 ppm, the content of iron element is controlled to be 25 ppm, the content of chromium element is controlled to be 10 ppm, the impurity content is less than 100 ppm, and the oxygen element content is less than 5 ppm. The ingot is a square ingot, and the thickness of the square ingot is 100 mm.
[0073] (2) the ingot in step (1) is sequentially preheated at 700 DEG C. and hot-rolled to obtain a hot-rolled material with a thickness of 10 mm.
[0074] (3) the hot-rolled base material in step (2) is coarsely rolled, the rolling pass number of coarse rolling is 15 passes, and the deformation rate of each pass of coarse rolling is controlled to be 20%, to obtain a coarsely rolled material with a thickness of 0.7 mm.
[0075] (4) the coarsely rolled material in step (3) is annealed at 650 DEG C. for 1 h to obtain an annealed material.
[0076] (5) the annealed material in step (4) is finish-rolled, the pass number of finish-rolling is 3 passes, and the deformation rate of each pass of finish-rolling is controlled to be 18%, to obtain an oxygen-free copper sheet for ceramic copper-clad plate with a thickness of 0.4 mm.
[0077] Embodiment 3
[0078] The embodiment provides a preparation method of oxygen-free copper sheet for ceramic copper-clad plate, and the preparation method comprises the following steps:
[0079] (1) melt and cast a copper plate raw material to obtain an ingot. The content of silver element in the ingot is controlled to be 40 ppm, the content of iron element is controlled to be 10 ppm, the content of chromium element is controlled to be 10 ppm, the impurity content is less than 100 ppm, and the oxygen element content is less than 5 ppm. The ingot is a square ingot, and the thickness of the square ingot is 200 mm.
[0080] (2) the ingot in step (1) is sequentially preheated at 900 DEG C. and hot-rolled to obtain a hot-rolled material with a thickness of 12 mm.
[0081] (3) the hot-rolled base material in step (2) is coarsely rolled, the rolling pass number of coarse rolling is 10 passes, and the deformation rate of each pass of coarse rolling is controlled to be 30%, to obtain a coarsely rolled material with a thickness of 0.7 mm.
[0082] (4) the coarsely rolled material in step (3) is annealed at 250 DEG C. for 3 h to obtain an annealed material.
[0083] (5) The material after annealing in step (4) is subjected to finish rolling, the number of passes of finish rolling is 2 passes, and the deformation rate of each pass of finish rolling is controlled to be 15%, to obtain the oxygen-free copper sheet for ceramic copper-clad plate with a thickness of 0.5 mm.
[0084] Example 4
[0085] The present example provides a preparation method of an oxygen-free copper sheet for ceramic copper-clad plate, which is the same as that of Example 1 except that the temperature of preheating is 950℃, and details are not repeated here.
[0086] Example 5
[0087] The present example provides a preparation method of an oxygen-free copper sheet for ceramic copper-clad plate, which is the same as that of Example 1 except that the temperature of preheating is 750℃, and details are not repeated here.
[0088] Example 6
[0089] The present example provides a preparation method of an oxygen-free copper sheet for ceramic copper-clad plate, which is the same as that of Example 1 except that the temperature of annealing treatment is 700℃, and details are not repeated here.
[0090] Example 7
[0091] The present example provides a preparation method of an oxygen-free copper sheet for ceramic copper-clad plate, which is the same as that of Example 1 except that the temperature of annealing treatment is 200℃, and details are not repeated here.
[0092] Comparative Example 1
[0093] The present comparative example provides a preparation method of an oxygen-free copper sheet for ceramic copper-clad plate, which is the same as that of Example 1 except that the deformation rate of each pass of rough rolling is controlled to be 40%, and details are not repeated here.
[0094] Comparative Example 2
[0095] The present comparative example provides a preparation method of an oxygen-free copper sheet for ceramic copper-clad plate, which is the same as that of Example 1 except that the deformation rate of each pass of finish rolling is controlled to be 40%, and details are not repeated here.
[0096] Comparative Example 3
[0097] The present comparative example provides a preparation method of an oxygen-free copper sheet for ceramic copper-clad plate, which is the same as that of Example 1 except that the annealing treatment of step (4) is performed after the finish rolling of step (5), and details are not repeated here.
[0098] Comparative Example 4
[0099] The comparative example provides a preparation method of oxygen-free copper sheet for ceramic copper-clad plate, which is the same as that of example 1 except that no annealing treatment is performed, and details are not repeated here.
[0100] Test method: the tensile strength and elongation of copper were tested according to GB / T 34505-2017, and the hardness of copper plate was tested according to GB / T 4340.1-2024.
[0101] The oxygen-free copper sheet for ceramic copper-clad plate obtained in the above examples and comparative examples was welded with Al2O3 ceramic, the bonding rate was evaluated by ultrasonic scanning, and the peel strength test was performed by a peel strength tester.
[0102] The test results of the above examples and comparative examples are shown in Table 1.
[0103] Table 1
[0104]
[0105]
[0106] From Table 1, the following points can be seen:
[0107] (1) The oxygen-free copper sheet for ceramic copper-clad plate and the mechanical property control method thereof provided by the application can make the final obtained oxygen-free copper plate meet the production and use of ceramic copper-clad plate, and the mechanical properties meet the bonding rate and peel strength of ceramic copper-clad plate, by controlling the processes of rough rolling, annealing and finished product finishing, especially the control of the deformation rate of each pass of rough rolling and the deformation rate of each pass of finishing, and cooperating with suitable preheating and intermediate annealing process.
[0108] (2) Comparative analysis of examples 1 and 4-5 shows that the application preferably controls the preheating temperature within a reasonable range, when the preheating temperature is too high, the peel strength of the finally obtained ceramic copper-clad plate is too low; when the preheating temperature is too low, the copper plate obtained is of poor shape, and the bonding rate of the ceramic copper-clad plate is seriously decreased.
[0109] (3) Comparative analysis of examples 1 and 6-7 shows that the application preferably controls the annealing temperature within a reasonable range, when the annealing temperature is too high, the hardness of the copper plate obtained is too low, and the tensile strength of the ceramic copper-clad plate is too low; when the annealing temperature is too low, the hardness of the copper plate obtained is too high.
[0110] (4)Comparative Example 1 and Example 1 can be seen that the copper plate prepared by Comparative Example 1 has high hardness, high tensile strength, poor plate shape, low ceramic copper clad plate welding bonding rate and low peeling strength; the copper plate prepared by Comparative Example 2 has high hardness, low ceramic copper clad plate welding bonding rate and low peeling strength; the copper plate prepared by Comparative Example 3 has obviously low hardness and low tensile strength because of the annealing treatment after the finish rolling of step (5); the copper plate prepared by Comparative Example 4 has high hardness, high tensile strength, low ceramic copper clad plate welding bonding rate and low peeling strength because of no annealing treatment.
[0111] The present application is described by the above examples to illustrate the detailed features of the present application, but the present application is not limited to the above detailed features, i.e. it does not mean that the present application must rely on the above detailed features to be implemented. It should be understood by those skilled in the art that any improvement of the present application, equivalent replacement of the selected technical features of the present application, addition of auxiliary technical features, selection of specific modes, etc. fall within the protection scope and disclosure scope of the present application.
Claims
1. A method for preparing oxygen-free copper sheets for ceramic copper-clad laminates, characterized in that, The preparation method comprises the following steps: (1) melting and casting a copper plate raw material to obtain an ingot; (2) sequentially preheating and hot-rolling the ingot of step (1) to obtain a hot-rolled material; (3) coarsely rolling the hot-rolled material of step (2), and controlling the deformation rate of each coarse rolling pass to be ≤30% to obtain a coarsely rolled material; (4) annealing the coarsely rolled material of step (3) to obtain an annealed material; (5) finish rolling the annealed material of step (4), and controlling the deformation rate of each finish rolling pass to be ≤35% to obtain an oxygen-free copper sheet for ceramic copper-clad plate.
2. The production method according to claim 1, characterized by, The copper plate raw material of step (1) comprises electrolytic copper and an additive metal; Preferably, the purity of the electrolytic copper is ≥4N; Preferably, the additive metal comprises any one or a combination of at least two of silver, iron or chromium.
3. The production method according to claim 1 or 2, characterized by, The content of silver in the ingot of step (1) is controlled to be 10-40ppm; Preferably, the content of iron in the ingot is controlled to be 10-25ppm; Preferably, the content of chromium in the ingot is controlled to be 10-25ppm; Preferably, the impurity content in the ingot is <100ppm; Preferably, the oxygen content in the ingot is <5ppm; Preferably, the ingot is a square ingot; Preferably, the thickness of the square ingot is 100-200mm.
4. The process according to any one of claims 1 to 3, characterized in that, The preheating temperature of step (2) is 700-900℃; Preferably, the thickness of the hot-rolled material is 10-12mm.
5. The process according to any one of claims 1 to 4, characterized in that, The rolling thickness of the coarse rolling of step (3) is 0.7-1.0mm; Preferably, the rolling pass number of the coarse rolling is 10-15 passes.
6. The method of any one of claims 1 to 5, wherein, The annealing temperature of step (4) is 250-650℃; Preferably, the annealing time is 1-3h.
7. The process according to any one of claims 1 to 6, characterized in that, The pass number of the finish rolling of step (5) is 2-3 passes.
8. The process according to any one of claims 1 to 7, characterized in that, The preparation method comprises: (1) melting and casting a copper plate raw material to obtain an ingot; the content of silver in the ingot is controlled to be 10-40ppm, the content of iron is controlled to be 10-25ppm, the content of chromium is controlled to be 10-25ppm, the impurity content is <100ppm, and the oxygen content is <5ppm; the ingot is a square ingot; the thickness of the square ingot is 100-200mm; (2) sequentially preheating and hot-rolling the ingot of step (1) at a temperature of 700-900℃ to obtain a hot-rolled material with a thickness of 10-12mm; (3) coarsely rolling the hot-rolled material of step (2), the rolling pass number of the coarse rolling is 10-15 passes, and the deformation rate of each coarse rolling pass is controlled to be ≤30% to obtain a coarsely rolled material with a thickness of 0.7-1.0mm; (4) annealing the coarsely rolled material of step (3) at a temperature of 250-650℃ for 1-3h to obtain an annealed material; (5) finish rolling the annealed material of step (4), the pass number of the finish rolling is 2-3 passes, and the deformation rate of each finish rolling pass is controlled to be ≤35% to obtain an oxygen-free copper sheet for ceramic copper-clad plate.
9. An oxygen-free copper sheet for a ceramic copper-clad plate, characterized by, The oxygen-free copper sheet for ceramic copper-clad plate is prepared by the preparation method of the oxygen-free copper sheet for ceramic copper-clad plate according to any one of claims 1-8. Preferably, the thickness of the oxygen-free copper sheet used in the ceramic copper-clad laminate is 0.3–0.5 mm; Preferably, the hardness of the oxygen-free copper sheet used in the ceramic copper-clad laminate is 90-120 Hv; Preferably, the tensile strength of the oxygen-free copper sheet used in the ceramic copper-clad laminate is 270–390 MPa; Preferably, the elongation of the oxygen-free copper sheet used in the ceramic copper-clad laminate is ≥2%.
10. A ceramic copper clad plate characterized by, The ceramic copper-clad laminate includes the oxygen-free copper sheet for ceramic copper-clad laminates as described in claim 9.
Citation Information
Patent Citations
Production technology of high-conductivity oxygen-free copper strip for ceramic copper-clad laminate
CN106216423A
Copper plate preparation method of ceramic copper-clad plate
CN116042983A
Cited By
Copper plate as well as preparation method and application thereof
CN121951273A